INFLUENCE OF TECHNOLOGY ON OTT SERIAL STORYTELLING: A STUDY ON THE PILOT OF SACRED GAMES - Pandian, Maruthu; M. R, Sathyaprakash (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The twentieth century has witnessed various kinds of technological innovations which have contributed to create different approaches to how stories are told visually. Every new film technology that has been invented, has pushed the boundaries of narrative techniques to a new direction. This study attempts to trace how different technologies at different periods of time have influenced the narrative process. It also seeks to investigate whether the twenty-first century’s most significant digital innovation, the internet, has contoured the approaches to screenplay writing and narration in Indian television storytelling. Complex TV, as proposed by Mittell (2015), marks the paradigm shift in American television, which occurred as a result of the internet and Video-on-demand services. By analyzing the pilot episode of the Indian OTT serial Sacred Games (2018), the study will analyse if the facets of complex TV which are already apparent in the West, are also present in Indian OTT services. It is found that the OTT streaming services in India have in fact given television programmes a special platform that goes beyond the restrictions of network airing. A pilot episode in the Indian OTT context, is found to have the following characteristics - establishing narrative thrust, guiding the viewers to watch the serial, and encouraging the process of continued consumption. These parameters were outlined by Mittell (2015) as requisites for complex TV. It is found that the poetics of complex TV has also made its way to Indian OTT series.